The principle of loyalty in EU law - Klamert, Marcus (Oxford : Oxford University Press, 2014)
The principle of loyalty requires the EU and its Member States to co-operate sincerely towards the implementation of EU law. Under the principle, the European courts have developed significant public law duties on States to deepen the reach of EU law. This text presents a full-length analysis of the loyalty principle and its legal implications.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 28, 2014).
Keywords: Constitutional law -- European Union countries; Loyalty; Law